El Excentrico, 1959-10-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
October 5, 1959 [5 de octubre de 1959]. Ano 10. No 3. Cover contains a photo of Mr. and Mrs. Gonzales giving toast. At the time of this issue's release, the couple was celebrating their 50th wedding anniversary. The headline reads, "Mr. and Mrs. Guillermo Gonzales celebrate 50th wedded year."